Efficient and reusable polyethylene oxide/polyaniline composite membrane for dye adsorption and filtration - Mansor, Eman S.; Ali, Heba; Abdel-Karim, Ahmed (Colloid and interface science communications, 2020)
The endless introduction of toxic dyes through industrialization has worsened the dyes pollution in the environment. As a consequence, the need for the effective removal of such dyes has become more crucial than before. Recently, polymeric membranes for dye adsorption are gaining tremendous attention. In this context, we synthesized the polyethylene oxide/polyaniline (PEO/PANI) composite membrane by a very simple and cost effective approach for the first time. The removal of methyl orange (MO) dye onto pure PEO and composite membrane was conducted utilizing batch mode. The results proposed that the uptake efficiency of PEO after hybridization with PANI is more than two times higher than that of the unmodified PEO membrane under the same experimental conditions. The effect of changing the adsorbent dose (1.5, 2, 2.5, 3 g/L), pH (3, 5, 6.5, 9, 11), and dye concentration (2.5, 5, 7.5, 10 mg/L) on the adsorption performance of the composite membrane was studied. The reusability studies proved that within 50 min of adsorption period the PEO/PANI composite membrane can retain 99% removal percentage for 8 cycles. This indicates that the low cost composite membrane has a good recyclability, which represents a crucial feature for the sorption technique to remove dyes from wastewater streams. Additionally, the proposed adsorption mechanism was discussed. Finally, the as-synthesized PEO and PEO/PANI was tested as a pressure filtration membrane using a cross-flow filtration system. The results revealed that the incorporation of PANI improved the dye rejection by 82.5% compared to that of the pure PEO membrane. [Display omitted] •Prosperous fabrication of efficient and reusable polyethylene oxide/polyaniline (PEO/PANI) as adsorptive membrane•Application of polyethylene oxide/polyaniline for methyl orange removal•Improving the performance of the PEO membrane with boosted adsorption capability•PEO/PANI can retain 99% removal percentage for eight cycles•The fabricated PEO/PANI membrane has higher rejection percent of MO during filtration process 82.5% compared to PEO